Contribution of DEAD-Box RNA Helicase 21 to the Nucleolar Localization of Porcine Circovirus Type 4 Capsid Protein - Zhou, Jianwei; Wang, Yuexia; Qiu, Yonghui; Wang, Yongxia; Yang, Xiaoyu; Liu, Changzhe; Shi, Yongyan; Feng, Xufei; Hou, Lei; Liu, Jue (Frontiers in Microbiology, 2022)
Porcine circovirus type 4 (PCV4) is a newly emerging pathogen which might be associated with diverse clinical signs, including respiratory and gastrointestinal distress, dermatitis, and various systemic inflammations. The host cellular proteins binding to PCV4 capsid (Cap) protein are still not clear. Herein, we found that the PCV4 Cap mediated translocation of DEAD-box RNA helicase 21 (DDX21) to the cytoplasm from the nucleolus and further verified that the nucleolar localization signal (NoLS) of the PCV4 Cap bound directly to the DDX21. The NoLS of PCV4 Cap and 763GSRSNRFQNK772 residues at the C-terminal domain (CTD) of DDX21 were required for this PCV4 Cap/DDX21 interaction. Further studies indicated that the PCV4 Cap NoLS exploited DDX21 to facilitate its nucleolar localization. In summary, our results firstly demonstrated that DDX21 binds directly to the nucleolar localization signal of the PCV4 Cap thereby contributing to the nucleolar localization of the PCV4 Cap protein.